Headlines-Narrative Techniques / By the end of this module students will be familiar with: The different types of travel article titles and the travel narratives - Γαλατσοπούλου Φανή (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2015)
By the end of this module students will be familiar with: The different types of travel article titles and the travel narratives: Παρακαλώ, αυτό είναι το πέμπτο μότυλο και το τίτλο «Κομμάτια και Ναρατηρικές Τεχνικές». Παρά το τέλος αυτού του μότουλου, οι φοιτητές θα είναι γνωστοί με τους διαφορετικούς τίτλους και τα κομμάτια. Παρακαλώ, αυτό είναι το πέμπτο μότυλο και το τίτλο «Κομμάτια και Ναρατηρικές Τεχνικές». Παρακαλώ, αυτό είναι το πέμπτο μότυλο και το τίτλο «Κομμάτια και Ναρατηρικές Τεχνικές». Είναι το τέτοιο που εφαρμόζει τη φυσική του αρτικού που υπάρχει κάτω και τι σημαίνει η ιστορία. Η δικαιοσύνη του είναι να προσφασίσουμε την ιστορία γρήγορα και μικρά. Ένα κομμάτι πρέπει να είναι ακριβό, συγκεκριμένο, απλό και εφαρμοσιακό. Υπάρχουν μερικά γενικά ρόλες της κομμάτιας που έχουν να κάνει με τον τύπο, τον γραμμα, τον σύνταξο, την πυγκτουρία και τις λόγες των λόγων. Ρόλες για το τι να γράψουμε και το τι να αποφασίσουμε. Κάποιες ρόλες είναι διαφορετικές αν γράψουμε κομμάτια για την εφαρμοσιακή, για την ιστορία ή για τα κοινωνικά μέτρα. Αλλά μπορούμε να έχουμε και διαφορετικές κομμάτια για την εφαρμοσιακή μέτρα, επειδή εφαρμόζεται από το γενικικό γενικό και τις τύπες των εφαρμοσιακών. Έχουμε διαφορετικές κομμάτια, ακόμα και για την ίδια ιστορία, σε ένα ταμπλόιτ ή σε ένα μπροτσίτ. Και έχουμε διαφορετικές κομμάτια σε εφαρμοσιακές εφαρμοσιακές και σε μαγαζίνες. Και, φυσικά, θα βάλουμε διαφορετικές κομμάτια σε μια νέα ιστορία, σε μια εφαρμοσιακή ιστορία, σε μια επεισοδοχή και σε μια επεισοδοχή. Κομμάτια ή κομμάτια σε εφαρμοσιακή μέτρα και σε κοινωνική μέτρα είναι ονομάζονται virtual gateways. Όλες τις τύπες και τις δραστηριότητες είναι εφαρμοσιακές και ειδικά σε κοινωνική μέτρα. According to Stovall, headlines are cryptic summaries of information that indicate the content of a longer piece. So, we have label headlines, descriptive headlines, commentative headlines, sidebars. These are related news stories that run along with the article with interrelated titles. And we have running stories headlines when we have, for example, progressive news stories. But how to write a headline, a title? There are some basic instructions for writing a headline. For example, to locate the focus point, to identify keywords and then write the title and rewrite the title many times until we're almost sure that we will attract the target group. And when we're out of ideas, we have to look up for examples. And we will find many different kinds of examples because travel journalism contains different kinds of writing genres and that's because travel journalism is in the intersection between information and entertainment, journalism and advertisement. So, different headline techniques are used. We should not also forget that we have many different types of travel articles that focus on different subject or themes. We have the creative non-writing travel articles such as personal experience essays or travel logs which offer the freedom to write many inspired titles. But on the other hand, we have the factual style travel writers like destination articles, food-related articles, travel advice or service articles, travel tips, special interest articles, journey articles or round-up articles. Let's see some examples of travel stories headlines. Let's start with the how-to headlines, the headlines that start with how-to. For example, how to travel with children or how to be part of the Polo club, how to use credit cards to travel for free, how to use local websites to save money on flights, how to quit your job and travel the world, how to visit Bali and have the time of your life. The questions are very popular in travel article titles. For example, why haven't you taken your dream trip yet? Italy versus Spain, which has better food? Do you recognize these places? Tired of hostels? Here's how to find posh apartments around the world. Young and broke? Seven reasons you love Southeast Asia. Another kind of headlines. People seem to like secrets. Whenever someone is ready to share a secret, we are all ears to hear it. So our example is about secret passages. And another example of Boston's Secret National Park. Lists are also very popular. They are easy to read, easy to understand. They attract the eye and make people curious to read the top three or top ten, the hot list or the gold list of the year. Our examples, the top ten countries for backpacking, the top ten rivers for rafting, three foods to eat before you die, eight monuments to see before you die. Numbers are also very usual in travel article headlines. For example, cultural trio, 25 reasons to go to Dublin, ten short breaks by train in Europe, five stylish budget weekend breaks. We find also headlines that contain film titles, as in our example, Eat, Pray, Love, Now Try the Holiday. And we can find also song titles, as our example here, Hippie Shake. The best of in headlines is also very popular title. Our example is of an article about an island, about the island Spetses in Greece. The best of Spetses. We find many the best of headlines in travel articles. In essays or personal experiences we can find other kinds of headlines. For example, ancient paths, the island of long life. Here you see more examples of travel stories headlines. You have to read as many travel articles you can, so that you gain some experience in headlines. After some time you will be able to write your own headlines, but first you need to get inspired. And that's what we offer in this course, inspiration. We offer an invitation to dive deeper into the world of travel journalism and communication and find your own way. Now, let us talk about the travel article writing. As travel writers admit, today's travel writing gives emphasis on non-narrative structures. Publishers also give emphasis on articles that have use value, that's why there are so many service articles or destination non-narrative articles. But we also have the narrative structures, the creative non-fiction articles that are travel stories, travel accounts. So, how do we tell a travel story? A creative non-fiction travel story. We need characters, the ones that the story involves, a setting where the story takes place, a plot, the sequence of events and a narrator. The narrator is the one who tells the story and the characters everyone else in the story. And what's the narrator's position in the story? When the narrator is involved in the story, then we have the first person narration, I and we. When the writer refers or addresses to the readers, to you, then the second person narration is used. The third person narration is used when the narrator is outside the story, he, she or they. Sometimes we may find dialogue and narration together in order to make the story more vivid. There are many storytelling techniques in travel stories as in all narrative forms. All we have to do is to read as many travel stories as we can in order to explore them. So, your first task is to find 10 factual style travel articles and 10 creative non-fiction style travel articles and comment their writing and narrative techniques. Upload them on our Facebook team, the links or the articles and your comments and let's talk about them. Your next task is about headlines. Find 20 travel article headlines that you really like, post them on Facebook and let's talk about them. And finally your creative task. Try to remember a very pleasant or a nasty experience during a trip of yours and tell us about it, tell us the whole story. Use any kind of tool or software you like and send us a video, an audio or text about your travel experience. Don't forget to find an appropriate title for it. So, our fifth module about headlines and narratives ends here. Don't forget our discussion continues online on social media.